2010
DOI: 10.4314/njps.v23i1-2.54929
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the delayed puberty onset in offspring of rats that consumed aqueous extract of hibiscus sabdariffa during pregnancy

Abstract: Summary: Consumption of extracts of Hibiscus sabdariffa (family: malvaceae) during pregnancy has been shown to cause maternal malnutrition which has been linked to various adverse conditions like increased postnatal weight gain, delayed puberty onset and elevated body weight and body mass index at onset of puberty in the female offspring. The present study was designed to investigate the possible mechanism underlying this. Eighteen in-bred pregnant Sprague-Dawley rats were on day 1 of pregnancy, randomly divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The consumption of the extract of H. sabdariffa during lactation is rich in flavonoids (Zheng et al, 2016), further increasing the concentration of active glucocorticoids. This event explains the raised corticosterone level, as observed in the study by Iyare and Adegoke (2008), and may contribute to the lactation process and thus enhance nutrient delivery to the suckling neonates.…”
Section: Discussionsupporting
confidence: 55%
“…The consumption of the extract of H. sabdariffa during lactation is rich in flavonoids (Zheng et al, 2016), further increasing the concentration of active glucocorticoids. This event explains the raised corticosterone level, as observed in the study by Iyare and Adegoke (2008), and may contribute to the lactation process and thus enhance nutrient delivery to the suckling neonates.…”
Section: Discussionsupporting
confidence: 55%
“…Neither the H. sabdariffa extract nor the anthocyanins significantly altered either testicular weight and histology, or uterus weight. Plasma concentrations of the three hormones, the testicular concentrations of protein, reduced glutathione and total cholesterol, and superoxide dismutase activity were all insignificantly affected by either the extract or the anthocyanins (66)(67) .…”
Section: Hibiscus Sabdariffamentioning
confidence: 92%
“…A few studies in rats have shown that consumption of the extract of Hibiscus sabdariffa during pregnancy and lactation results in increased postnatal weight gain, delayed onset of puberty and elevated body mass index at onset of puberty, in female offspring [6][7][8][9]. Maternal and early life nutritional cues seem to "program" the developmental trajectory of a child by augmenting the timing of puberty onset for reproductive advantage in a predicted poor environment [10].…”
Section: Introductionmentioning
confidence: 99%